1971
DOI: 10.2343/geochemj.4.123
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of rhenium in molybdenites from Japan

Abstract: The rhenium contents of about 200 molybdenites have been determined by the neutron-activation or the catalytic spectrophotometric analyses. The present authors developed these methodes for the determination of the rhenium content of a very wide range, taking only a small amount of each sample.The data obtained show that 1) the rhenium content of molybdenite covers the range from 10-8 to 7 X 10-3 in atomic ratio of Re/Mo, 2) the rhenium contents generally decrease with the following order of occurrence of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0
1

Year Published

1974
1974
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 15 publications
3
10
0
1
Order By: Relevance
“…Electron-microprobe data (Table 1) show that molybdenite in quartzmolybdenite veinlets contain up to 4.7 wt% Re, which is consistent with the analyses of Arikas (1979) and Melfos et al (2001). There is an almost perfect linear correlation between the Mo and Re content of molybdenite, supporting the concept previously proposed (e.g., Fleischer 1959, Terada et al 1971, Stein et al 2001 that Re substitutes for Mo in the structure of molybdenite (Fig. 4).…”
Section: Composition Of Rheniite and Re-bearing Molybdenitesupporting
confidence: 74%
See 1 more Smart Citation
“…Electron-microprobe data (Table 1) show that molybdenite in quartzmolybdenite veinlets contain up to 4.7 wt% Re, which is consistent with the analyses of Arikas (1979) and Melfos et al (2001). There is an almost perfect linear correlation between the Mo and Re content of molybdenite, supporting the concept previously proposed (e.g., Fleischer 1959, Terada et al 1971, Stein et al 2001 that Re substitutes for Mo in the structure of molybdenite (Fig. 4).…”
Section: Composition Of Rheniite and Re-bearing Molybdenitesupporting
confidence: 74%
“…The mechanism for the deposition of rhenium and the physicochemical conditions of sulfide deposition are considered in the context of fluid-inclusion data. Geological and geochemical comparisons will be made with the rheniite-and rhenian-molybdenite-bearing sublimates of active intRoDUCtion Molybdenite is the major repository of Re in the Earth's crust, where it occurs in a solid solution toward the end member ReS 2 (e.g., Terada et al 1971, McCandless et al 1993. In general, the Re content of molybdenite is of the order of ppb to a few thousand ppm.…”
Section: (Traduit Par La Rédaction)mentioning
confidence: 99%
“…Table 1 also includes data from other Greek porphyry systems (e.g., Skouries, Fakos, Sardes, Stypsi) and from molybdenite in porphyry Cu, Cu-Au, Cu-Mo and Mo deposits elsewhere. The almost perfect linear correlation between the Mo and Re content of molybdenite (Figure 6b) indicates that Re substitutes for Mo in the structure of molybdenite as previously suggested [13,[21][22][23]. This is also evident from the homogeneous Re distribution in molybdenite (Figure 7a-c).…”
Section: Mineralogy Of Rhenium-bearing Phasessupporting
confidence: 59%
“…Rhenium contents in molybdenites vary greatly (Terada et al, 1971;Fleischer, 1960). Mao et al (1999) suggested that the Re contents of molybdenite could reflect the source of the deposits with Re content decreasing from mantle to I type and to S type granite-related deposits.…”
Section: Rhenium Concentrations In Molybdenitementioning
confidence: 97%